The headless ghost - Stine, R. L. (New York : Scholastic, 1995)
Hill House is the biggest tourist attraction in town because it's haunted by the ghost of a headless thirteen- year-old boy. Duane and Stephanie have never seen the ghost so one night they decide to go on a search for his head.
RL4.
008-012.
440
Accelerated Reader AR
Keywords: Ghosts -- Fiction; Horror stories